Neuraxial Anesthesia and the Ubiquitous Platelet Count Question: How Low Is Too Low?. Issue 4 (December 2021) - Scavone, B.M.; Wong, C.A.
Abstract : ( Anesth Analg . 2021;132:1527–1530) Recently, the Society for Obstetric Anesthesia and Perinatology (SOAP) issued a consensus statement regarding neuraxial procedures in patients with thrombocytopenia. When considering the cutoff platelet count for providing neuraxial labor analgesia or neuraxial anesthesia for cesarean, this statement might not provide clinicians with all the answers.